Lloyd V. Berkner papers - Berkner, Lloyd V. (Lloyd Viel), 1905-1967.
Correspondence, speeches, biographical material, financial records, newspaper clippings, photographs, and other papers relating to Berkner's career as an engineer and physicist and to the International Geophysical Year, 1957-1958. Organizations represented include the American Geophysical Union; Institute of Electrical and Electronics Engineers; Institute of Radio Engineers; International Council of Scientific Unions; International Geophysical Committee, International Council of Scientific Unions; International Union of Radio Science; National Academy of Sciences (U.S.); and Space Science Board, National Academy of Sciences (U.S.).
Physicist, engineer, and administrator.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room.
Keywords: American Geophysical Union; Institute of Electrical and Electronics Engineers; Institute of Radio Engineers; International Council of Scientific Unions; International Council of Scientific Unions. -- International Geophysical Committee; International Union of Radio Science; National Academy of Sciences (U.S.); National Academy of Sciences (U.S.). -- Space Science Board; Electrical engineering; Electrical engineering -- Societies, etc; Geophysics; Geophysics -- International cooperation; Geophysics -- Societies, etc; International Geophysical Year, 1957-1958.; Radio; Radio -- Societies, etc; Science; Science -- Societies, etc; Space sciences; Space sciences -- Societies, etc; Administrators; Engineers; Physicists